A Blancan (Pliocene) short-faced bear from El Salvador and its implications for Tremarctines in South America - Soibelzon, Leopoldo Héctor (2008)
We present here a deciduous tooth recovered from the Blancan (Pliocene) Río Tomayate locality (Republic of El Salvador) and assign it to cf. Arctotherium (South American short-faced bears) based on its morphology and size. Carnivores, like many other taxa, entered South America from North America during the “Great American Biotic Interchange” (GABI). We think that this individual was part of the stock that entered South America and may have been ancestral to later Arctotherium species. It has been postulated that Arctodus and Arctotherium are sister groups that make up the “short-faced bears clade”. Until now, Arctotherium had only been recorded in South America; the oldest record corresponds to Arctotherium angustidens from the Ensenadan (Early to Middle Pleistocene) of the Pampean Region of Argentina; 5200 km from the Panamian Isthmus. Among Ensenadan sediments the oldest ones are those of “las toscas del Río de La Plata” locality (Pampean Region). The age of these sediments is 1Ma and they correspond to Chron C1r2r. In the northern portion of South America (Venezuela) Arctotherium specimens are only recorded from the Late Pleistocene. Thus, the new specimen provides the earliest record of Arctotherium, extends the distribution of this taxon to Central America and may represent the basal stock for short-faced bears in South America.